ON SOME SYSTEM OF PROPOSITIONAL LOGICS CALCULUS - Chubaryian, A. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this paper generalizations of "modus ponens" rules are defined on the basis of which a certain system of propositional logics calculus is constructed to which both the Frege systems and the Frege systems with substitutions are polynomially brought.